Báo cáo tóm tắt dự án Hồ chứa nước Ka Pét, huyện Hàm Thuận Nam, tỉnh Bình Thuận - Uỷ ban nhân dân tỉnh Bình Thuận (2022)
Toàn văn Báo cáo tóm tắt dự án Hồ chứa nước Ka Pét, huyện Hàm Thuận Nam, tỉnh Bình Thuận.